2021
DOI: 10.3389/fpubh.2021.606050
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Intertemporal Socioeconomic Inequalities in Alcohol Consumption in South Africa

Abstract: Background: This paper assesses changes in the socioeconomic inequality in alcohol consumption by exploring whether alcohol consumption (current and binge drinkers) is more prevalent among the wealthier (pro-rich) or poorer (pro-poor) group over time.Methods: Data come from the 2008, 2010/11, 2012, and 2014/15 waves of the National Income Dynamics Study (NIDS). Various equity stratifiers (sex, age, race, and rural/urban) are used to analyze the prevalence of alcohol consumption and to investigate differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Tis study aimed to identify the existence of socioeconomic inequalities in alcohol and tobacco consumption and of correlation at the ecological level of state prevalences of alcohol and tobacco consumption in Mexican elementary and middle-school adolescents aged 10-16 years, verifying the hypothesis that there is a positive and signifcant correlation between these two events. Although the results did not show the existence of socioeconomic inequalities in alcohol consumption, as observed in other studies, including prorich inequality [50][51][52], they were observed for tobacco consumption. We must take into account that there are a variety of factors at the individual/household level (for example, age, education, and income) and the societal level (for example, taxation policy, ease of alcohol availability, and norms around alcohol consumption) that infuence alcohol/ tobacco consumption.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Tis study aimed to identify the existence of socioeconomic inequalities in alcohol and tobacco consumption and of correlation at the ecological level of state prevalences of alcohol and tobacco consumption in Mexican elementary and middle-school adolescents aged 10-16 years, verifying the hypothesis that there is a positive and signifcant correlation between these two events. Although the results did not show the existence of socioeconomic inequalities in alcohol consumption, as observed in other studies, including prorich inequality [50][51][52], they were observed for tobacco consumption. We must take into account that there are a variety of factors at the individual/household level (for example, age, education, and income) and the societal level (for example, taxation policy, ease of alcohol availability, and norms around alcohol consumption) that infuence alcohol/ tobacco consumption.…”
Section: Discussioncontrasting
confidence: 89%
“…We must take into account that there are a variety of factors at the individual/household level (for example, age, education, and income) and the societal level (for example, taxation policy, ease of alcohol availability, and norms around alcohol consumption) that influence alcohol/tobacco consumption. However, in the world, socioeconomic status remains one of the most important social determinants of alcohol-attributable harm [ 51 ]. Over time, certain variations in the prevalence of consumption of these substances have been reported in Mexico [ 17 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may correspond to established social norms around drinking in the Cape Town region, where binge drinking is common, especially among young individuals with lower socioeconomic status. 50 , 51 There may also be higher levels of stigma associated with drinking in Uganda relative to SA. 52 This could contribute to underreporting of alcohol use, which was observed among non-pregnant participants in the Ugandan sample 53 of the parent study.…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse is known to be particularly problematic in South Africa (Ellis et al, 2013;World Health Organization, 2018), and the interaction between substance abuse and other social and economic problems, along with the impacts on children's development (e.g. from prenatal exposure to alcohol and/or drugs) are well documented (Ellis et al, 2013;Fontes Marx et al, 2021). These social and economic risks relate to the di culty observed that many caregivers struggle to meet the basic needs of their young children, and hence limit their ability to provide adequate nutrition and promote good health.…”
Section: Discussionmentioning
confidence: 99%